INTEGRASI TRADISI SEDEKAH BUMI DAN LAUT PADA PEMBELAJARAN SKI DI MADRASAH IBTIDAIYAH - Akhmad Aji Pradana; Nurhaningtyas Agustin; Alvina Putri (STKIP Pesisir Selatan, 2025)
Objective: This study aims to explore the values contained in the Sedekah Bumi and Sedekah Laut traditions in Tuban Regency and analyze their integration into Islamic Cultural History (SKI) learning in Madrasah Ibtidaiyah (MI). Methods: The study uses a qualitative approach with ethnographic and case study research types. Data collection was conducted through observation, semi-structured interviews with community leaders, teachers, and MI students, as well as documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Results: The results of the study show that the traditions of Sedekah Bumi and Sedekah Laut contain religious-spiritual, socio-cultural, environmental awareness, and educational values that function as a medium for intergenerational value transfer. The integration of these traditions into SKI learning was found in the form of contextualization of Islamic history material, particularly on the themes of socio-cultural transformation and Islamic preaching, although its implementation has not been fully structured in formal learning tools. Novelty: This study concludes that the Sedekah Bumi and Sedekah Laut traditions have the potential to become a source of local wisdom-based learning that is relevant for strengthening contextual, moderate, and meaningful SKI learning in Madrasah Ibtidaiyah.